Factors Affecting Effective Waste Management Practices in Owerri West Local Government Area (L.G.A.) of Imo State - K., Agwu; A., Osuagwu; B. U., Nnadozie; M. U., Akpaka (International Journal of Real Estate, 2025)
This study sets out to evaluate the factors affecting effective waste management practices in Owerri West L.G.A. of Imo State, with the intention of proffering better solutions to the problems. The objectives are; to identify the prevailing methods of waste management in Owerri West L.G.A., Imo State; to evaluate the effects of the prevailing waste management practices in Owerri West L.G.A., Imo State; to evaluate the factors affecting effective waste management practices in Owerri West L.G.A, Imo State and to examine effective waste management practices that can be useful in Owerri West L.G.A., Imo State. The study adopted a quantitative approach having explored the descriptive survey design using questionnaires to elicit answers from the population. 71 respondents returned their questionnaires and they were analysed. It was found that poor funding is a major impediment to effective waste management practice in Imo State. Out of 71 respondents who returned their questionnaires of the same number distributed, 26 (65%) noted that poor funding is the major issue with effective waste management practice in Imo State.  What that implies is that engaging modern automated facilities will be very hard to come by. It recommended that public private partnership plan (PPPP) should be encouraged to boost the funding-base for waste management practices in Imo State.
Keywords: Waste Management; Public Private Partnership; Effective Management